A pilot study of multimodal MRI for the preoperative assessment of triple-negative breast cancer - Luo, Shan; Lin, Rong; Lin, Hui; Zhan, Zejuan; Wu, Xiaomin; Tang, Langlang; Huang, Xionghua; Liu, Yuanying; Li, Pengfei; Yao, Junye; Wu, Peng; Liao, Xueyan (Frontiers in Oncology, 2026)
ObjectivesTo evaluate the diagnostic value of multimodal MRI by comprising quantitative mapping, diffusion-weighted imaging (DWI), and dynamic contrast-enhanced MRI (DCE-MRI) in differentiating triple-negative breast cancer (TNBC) from non-TNBC, and to investigate the correlation between significant quantitative mapping parameters and the Ki-67 proliferation index.MethodsThis prospective study enrolled 120 patients with invasive breast cancer (30 TNBC and 90 non-TNBC) who underwent preoperative quantitative mapping, DWI, and DCE-MRI. DCE-MRI parameters (RE, ME, MRE, T0, TTP, WI, WO, BOE), DWI metrics (ADCmin, ADCmean, rADCmin, rADCmean), and quantitative mapping parameters (Native T1, Enhanced T1, ΔT1, ΔT1%, T2) were compared between groups. Diagnostic performance was evaluated using receiver operating characteristic (ROC) analysis and area under the curve (AUC) for both individual significant parameters and a combined predictive model. Pearson’ s correlation coefficient was used to analyze the relationship between quantitative mapping parameters and the Ki-67 index.ResultsCompared to the non-TNBC group, TNBC lesions exhibited significantly lower RE, ME, WI, WO, and ΔT1% (p < 0.05), but higher Enhanced T1 and T2 values (p < 0.05). The combined model integrating DCE-MRI and quantitative mapping achieved the highest diagnostic accuracy (AUC = 0.977), outperforming DCE-MRI alone (AUC = 0.951) and quantitative mapping alone (AUC = 0.864), with sensitivity and specificity of 93.3% and 92.2%, respectively. In TNBC, the Ki-67 index showed a weak positive correlation with Enhanced T1 (r = 0.387, p < 0.05) and T2 (r = 0.381, p < 0.05).ConclusionParameters including RE, ME, WI, WO, Enhanced T1, ΔT1%, and T2 serve as valuable imaging biomarkers for the preoperative identification of TNBC. Integrating quantitative mapping with DCE-MRI significantly enhances diagnostic performance, offering a robust approach for differentiating TNBC from non-TNBC subtypes.